CADASTRAL VALUATION BASED UPON THE ENVIRONMENTAL FACTORS USING THE CITY OF KURSK AS AN EXAMPLE - Novikova, Tatyana; Khaustov, Vladimir; Guseinov, Teimur (Journal of Applied Engineering Science, 2018)
Economic appraisal of urban lands requires cartographic documents and point assessment. The purpose of the present studies is the creation of thematic cadastral maps and accompanying material. There were used the methods of mathematical statistics, comparative analysis, map modeling. The result of these studies can be used while making a comprehensive economic assessment of a city based on the existing regulatory framework. This article focuses on the environmental impact as one of the factors of integrated cadastral valuation.